Computer modeling studies on bioactive and novel natural products - Noorbatcha, Ibrahim Ali; Awang, Khalijah; Mohamad , Nurul Azmi; Mohamad, Khalit (2010)
Computational chemistry is a branch of chemistry that uses principles of computer science to assist in solving chemical problems. Structures and properties of molecules can be calculated when theoretical chemistry is incorporated into efficient computer programs. Its necessity arises from the well-known fact that apart from relatively recent results concerning the hydrogen molecular ion, the quantum n-body problem cannot be solved analytically, much less in closed form. While its results normally complement the information obtained by chemical experiments, it can in some cases predict hitherto unobserved chemical phenomena. It is widely used in the design of new drugs and materials. Examples of such properties are structure (the expected positions of the constituent atoms), absolute and relative (interaction) energies, electronic charge distributions, dipoles and higher multipole moments, vibrational frequencies, reactivity or other spectroscopic quantities, and cross sections for collision with other particles. In these studies, the 3D QSAR of rhazinilam (1) with an activity involving disassembly of microtubules and its derivatives was investigates by using comprehensive molecular field analysis (CoMFA). The results indicated a correlation between the antitubulin activity and the steric and electrostatic factors, which modulate their biological activity, and accounted for the potent activities of 1 with suitable relationship for the overall conformation. We have also modelled the apotirucallane triterpenes (2-6) using various quantum chemical methods, namely MNDO, AM1 and PM3 methods in vacuum and using AM1-SM2.1 method in solution. In this calculation, we find that the inclusion of solvation effects of the polar side chain is crucial for the interpretation of NMR data. By using the calculated interatomic distances, we are able to assign all NOE signals to the appropriate proton. Lastly, we were able to determine the relative configuration of the bisindoline, N-[N’-acetyl-7,7’-bis-(3,4-dimethoxy-bhenyl)-7,8,7’,8’-tetrahydro-N’H-[8,8’]biindolyl-N-yl]-ethanone (7) by using annealing method and semi-empirical AM1 calculations.